Numerical study of joint magnetisation and gravitational convection of air in a cubic enclosure with an inclined electric coil. (6th April 2005) - Bednarz, T.; Tagawa, T.; Kaneda, M.; Ozoe, H.; , J.S. Szmyd
Numerical computations were carried out for thermal convection of air in a cubic enclosure under both magnetising and gravitational fields. A one-turned circular coil with electric current, which induces a magnetic field, was placed around the enclosure and inclined with its plane oblique to the hot and cold walls and with its centre at the centre of enclosure. Computations were carried out for several combinations of parameters: Pr = 0.71; Ra = 1.51 × 10 4, 9.06 × 10 4 ; γ = 10, 30, 60, 100; γeuler from - π/2 to π/2.